Regional Development : Lessons from International Experience Applicable for Kazakhstan - Akkaya, Sebnem (World Bank, Washington, DC, 2014)
The first concerns the objective of regional development. International experience and the vast literature on economic geography suggest that as Kazakhstan transforms itself from a middle income country to a high income country, the spatial distribution of economic activity will continue to be uneven. Growth will be concentrated in a few leading cities and regions, as firms take advantage of agglomeration economies and workers migrate seeking higher wages. The second finding concerns the instruments of regional policy. Much of the discussion of regional policies focuses on the use of geographically-targeted subsidies or financing aimed at encouraging investment in lagging regions. But the World Bank's experience shows that this emphasis is too narrow. The most important policies that affect the growth of a region may not be those that are geographically targeted. The third finding concerns the design of regional development financing mechanisms. While regional development grants play, at best, an ancillary role in the economic development of lagging regions, they can be an important source of financing. Finally, the World Bank has learned that Municipal Development Funds (MDFs) may require reforms at the local level. Local governments vary in their capacity to prepare 'bankable' projects.